Relationship of Cell Envelope Stability to Substrate Capture in a Marine Psychrophilic Bacterium - Geesey, Gill G. (1981)
Cells of a psychrophilic marine bacterium were found to take up a variety of amino acids from seawater. Some of the amino acids that were taken up were released when the cells were exposed to a hypotonic salt solution. The proportion that was released varied according to the amino acid. A pool of the amino acid arginine that was formed during very short periods of exposure of cells to the exogenously supplied amino acid was particularly sensitive to reductions in salinity. In general, exposure to hypotonic salt solutions also resulted in reduced amino acid uptake by the cells. Complete removal of seawater salts (SE treatment) produced obvious structural alterations in the cell envelope, resulting in an even greater reduction in amino acid uptake. Under these conditions, amino acid-binding components were released by the cells. Differential centrifugation and fluorescent antibody studies indicated that arginine-binding components are located on or near the surface of intact cells. The data suggest that substrate receptors were sensitive to reductions in seawater salt concentrations and that lesions at this level affected the organism's substrate uptake and retention capabilities.